Effect of Using Modern Banking Services on Customer Inspiration: Statistical Analysis - Moqdad Ibrahim Jassem; Rafiduraida Abdul Rahman; Abdelrahman Mohamed Ibrahim (Advances in Materials Science and Engineering)
Customer inspiration has recently gained much interest in marketing theory due to its consistent results as a customer management technique. Herein, the relationship between banking services and customer inspiration through the role of gender moderation is presented. Structural equation modelling through partial least squares modelling (PLS-SEM) has been employed to determine the nature of relationships between variables. Six hundred and forty questionnaires are distributed to branches of ten banks distributed in nine major cities in Iraq, including the capital, Baghdad. Data collection took 62 days; 394 complete answers (i.e., 61.56%) are collected. The approximate viability was evaluated by analyzing the average values of the extracted AVE contrast, where the average AVE was greater than 0.5 for all formulations. The findings show that banking services have a significant positive effect on inspiration and that gender has a positive role in mediating the relationship as a moderation variable.